You abuse but I will stay: The combined effects of job stress, customer abuse, and emotional intelligence on employee turnover - Muhammad, Kashif; Braganca, Eliane; Zainudin, Awang; Ernest Cyril, de Run (Emerald Publishing Limited, 2017)
Purpose – The purpose of this paper is to investigate the combined effects of customer aggression, job stress, and emotional intelligence (EI) on job satisfaction and organizational turnover among managers from a developing country, i.e. Pakistan. Design/methodology/approach – Data are collected from 230 respondents working as bank managers in Pakistan by means of a cross-sectional survey. The collected data are analyzed by employing a structural equation modeling (SEM) technique. Findings – The employees perceive that job stress positively influences emotional exhaustion among employees. Furthermore, EI negatively influences job exhaustion to minimize the potential to lead it through to organizational turnover. Originality/value – The combined effects of customer- and organization-related elements have been scarcely investigated – the heart and soul of contribution regarding this research. The moderation of EI to lessen the emotional exhaustion is a significant contribution to this study. Finally, the context of Pakistan’s banking sector is also unique to this study.